Students' Perception of Learning Vashmid Model of Japanese Pronunciation Through Online Mode - Yuli Wahyuni (Journal of Japanese Language Education and Linguistics, 2024)
Language acquisition is intricately connected to mastering pronunciation. Japanese pronunciation acquisition is mostly implemented through drill techniques and repetition activities. Drill approach is seen suitable for enhancing pronunciation skills due to its emphasis on language skills. Learning using drill techniques has traditionally been conducted in face-to-face or offline settings. Technological progress and the pandemic have led to an increase in online learning. Researchers aim to study Japanese pronunciation acquisition through online methods that had previously been conducted in person. This study aims to identify the students' perceptions and challenges encountered when learning pronunciation using online methods. The research employed a descriptive qualitative method by administering questionnaires to 15 students from the Japanese Language Education Study Program at Universitas Muhammadiyah Yogyakarta. These students had undergone pronunciation instruction utilizing the VASHMID paradigm in an online setting. Most students in the study believe that learning pronunciation effectively is achievable through online methods. The pupils have successfully predicted and prepared for any challenges that may arise during online learning.